Bacillus cereus var. Toyoi e Bacillus subtilis C-3102 no cultivo de tilápia do Nilo da linhagem GIFT - Moura, Milton Cézar de (2011)
This study aimed to evaluated the use of probiotics Bacillus cereus var. Toyo and Bacillus subtilis C-3102 added to the diet for juvenile Nile tilapia strain of GIFT (Genetically Improved Farmed Tilapia) in order to verify the colonization of the gut epithelium and water, the influence on the bacterial microflora, the production performance, the indexes of body composition, the chemical composition and parameters of water quality. Two experiments were conducted: culture in cages with young individuals by 127 days (E1) and culture in ponds with adults by 201 days (E2). There was used the Center for Environmental Research in Aquaculture (CPAA/Toledo-PR) twenty ponds with 8.4 m3 of water and cages with useful volumes of 0.175 m3. The fishes from each experiment were randomly assigned to four treatments with five replicates. The treatments consisted of diets for each phase of commercial cultivation, added 0.5% B. cereus var. Toyoi (BC), 0.5% B. subtilis C-3102 (BS), 0.5% of the combination of two probiotics (BC+BS) and without addition probiotics (SP). In experiment E1, it was found that B. cereus var. Toyo and B. subtilis C-3102 colonized the gut epithelium of fishes and water culture, but did not influence the other parameters (P > 0.05). Survival ranged from 80% to 90% and feed conversion of 1.69 ± 0.29 to 1.96 ± 0.94 for treatments BS and SP. The CP levels ranged from 13.08% to 13.78% for BC and BC+BS and vicerosomatic index ranged from 9.71% to 10.9% for BS and BS+BC, respectively. In experiment E2 was also observed that the probiotics colonize the intestines and water cultivation, but did not influence the other parameters (p > 0.05). In this experiment, the indexes of production performance were influenced by the average temperature of the water that stood at 20.7ºC and is below the optimal range for the species. Weight and specific growth of the fishes ranged from 324.81 g day-1 and 398.51 g day-1, and 0.62% day-1 to 0.73% day-1, respectively, for BC and BS. Feed conversion ranged from 2.40 ± 0.24 to 2.92 ± 0.41 for BS and BC and survival ranged from 84.5% to 86% for BC and SP. The probiotics B. cereus var. Toyo and B. subtilis C-3102 used individually and in combination colonized the gut epithelium of fishes and cultivation water, however, did not influence the gut microflora, the production performance, the indexes of body composition, the chemical composition and parameters of water quality.